TI_GERICHTE 11.2010.42 vom 6. November 2012 , Azione di manutenzione di un proprietario gravato da un diritto di passo pubblico - TI Tribunale d'appello (2012)
Azione di manutenzione di un proprietario gravato da un diritto di passo pubblico